Coping Strategies of International Chinese Undergraduates in Response to Academic Challenges in U.S. Colleges. Issue 2 (February 2018) - Heng, Tang T.
Background/Context: One in three international students in the U.S. comes from China, propelled by a steep increase in undergraduate enrollment in U.S. colleges. This phenomenon has been accompanied by negative media discourse that portrays them as needy, passive, and unable to cope with their new educational demands. Purpose/Objective: Using a hybrid sociocultural framework that privileges student agency and locates students within their sociocultural milieu, this study investigated strategies Chinese international undergraduates used to cope with challenges they faced in U.S. colleges. Population/Participants: Eighteen participants—nine freshmen and nine sophomores— from three liberal arts colleges situated in an urban context took part in the study. Research Design: This qualitative study followed participants through one academic year. Participants completed a demographic questionnaire, engaged in three semi-structured interviews at the beginning, middle, and end of their academic year, and wrote four journal prompts. Findings/Results: Results reveal that student strategies cluster around themes of agency and self-reliance, as well as outreach and support. Students spent more time studying, used a range of learning techniques, developed self-help and psychological strategies, tapped into institutional and technological support, and reached out to teachers and peers for help. Conclusions/Recommendations: Students' coping strategies reveal fluid responses to intersecting and changing sociocultural expectations, nimbleness in their adaptations, and transience in the challenges faced. Other than contesting stereotypes around Chinese students, findings spell implications for differentiated and responsive college policies serving international students, faculty members, and local peers. It also points to the need to incorporate more longitudinal studies with clear conceptual frameworks so that novel and nuanced understanding of international students can emerge.